PENGARUH TRANSPARANSI DAN AKUNTABILITAS TERHADAP PENINGKATAN KINERJA PENGELOLAAN PAJAK DAERAH PADA DINAS PENGELOLA KEUANGAN DAN ASET DAERAH (DPKAD) KOTA LHOKSEUMAWE - Muhammad Kautsar; Mulia Andirfa; Bobby Rahman (Jurnal Akuntansi dan Pembangunan (JAKTABANGUN) STIE Lhokseumawe, 2017)
This study on the Effects of Transparency and Accountability Improved Performance Against Local Tax Management at the Office of Financial Management and Asset (DPKAD) Kota Lhokseumawe. The purpose of this study is to examine the effect of transparency and accountability on the performance management of local taxes at the Department of Finance and Asset (DPKAD) Kota Lhokseumawe. The data used in this study a questionnaire to 47 employees who serve as research samples. The data processing is done with the help of multiple linear regression model using SPSS version 17. The results showed that the transparency and accountability affect the increased performance of the management of local taxes at the Department of Finance and Asset (DPKAD) Kota Lhokseumawe.